Circular Behaviours of Polish Consumers in Relation to Electrical and Electronic Products - Elzbieta Szczygiel (Amfiteatru Economic, 2023)
The article presents the concept of circular behaviours as part of the implementation of the circular economy in the daily life of households. These behaviours are considered in relation to electrical and electronic products. The aim of this article is to analyse the relationship between the taking up of certain behaviours in relation to these types of products and their selected effects in the form of benefits perceived by the household. The article presents the results of the research carried out among Polish households in two regions (N=400). Using statistical analysis methods (i.e., analysis of correlation, Chi2 independence test, Kruskal-Wallis ANOVA, U Mann-Whitney Test), three research hypotheses were inferred in relation to 13 circular behaviours and 4 benefits. The results showed that: (1) more frequent circular behaviour for one product results in repetition of this type of behaviour for others, (2) households undertaking circular behaviour more frequently (whether in general or specific) experience higher levels of benefit to their household, (3) socio-demographic characteristics differentiate households' adoption of circular behaviour to a limited extent, which applies only to selected aspects or to selected behaviours.
Keywords: D12; D16; D91; 330; Circular behaviours; electronic equipment; households; statistical analysis; Poland.